2018
DOI: 10.1200/jco.2018.78.7994
|View full text |Cite|
|
Sign up to set email alerts
|

Improvement in Overall Survival in a Randomized Study That Compared Dacomitinib With Gefitinib in Patients With Advanced Non–Small-Cell Lung Cancer and EGFR-Activating Mutations

Abstract: Purpose ARCHER 1050, a randomized, open-label, phase III study of dacomitinib versus gefitinib in treatment-naïve patients with advanced non-small-cell lung cancer (NSCLC) and activating mutations in EGFR, reported significant improvement in progression-free survival with dacomitinib. The mature overall survival (OS) analysis for the intention-to-treat population is presented here. Patients and Methods In this multinational, multicenter study, patients age 18 years or older (≥ 20 years in Japan and Korea) who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
327
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 391 publications
(341 citation statements)
references
References 19 publications
10
327
0
4
Order By: Relevance
“…Mutations in the epidermal growth factor receptor gene (EGFR) are the most common and actionable molecular aberrations in non-small cell lung cancer (NSCLC). [1][2][3] Epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) are effective in the treatment of advanced lung cancers harbouring EGFR mutations (EGFRm), [4][5][6][7] but remain expensive especially given continuous dosing for the duration that a patient benefits from these TKIs. 8,9 Efficacy of these EGFR-TKIs is not in question.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in the epidermal growth factor receptor gene (EGFR) are the most common and actionable molecular aberrations in non-small cell lung cancer (NSCLC). [1][2][3] Epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) are effective in the treatment of advanced lung cancers harbouring EGFR mutations (EGFRm), [4][5][6][7] but remain expensive especially given continuous dosing for the duration that a patient benefits from these TKIs. 8,9 Efficacy of these EGFR-TKIs is not in question.…”
Section: Introductionmentioning
confidence: 99%
“…First generation (gefitinib, erlotinib) and second generation (afatinib, dacomitinib) EGFR-TKIs have demonstrated improved progression-free survival (PFS), objective response rates, and tolerability when compared to first-line platinum doublet chemotherapy. [4][5][6][7] However, acquired resistance to EGFR-TKIs develops over time. The most common mechanism of resistance leading to failure of first-and second-generation TKIs is a secondary mutation in the EGFR gene, Thr790Met (T790M), found in up to 60% of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to many other carcinomas, NSCLC is united by having multiple genetic abnormalities, such as the epidermal growth factor receptor (EFGR) and c-ros oncogene 1 (ROS1) mutations, and those genetic features also contribute to the improvement pf NSCLC management. [13][14][15][16] Besides these altered genes, a diverse class of protein biomarkers also exist in the development of individualized treatment of NSCLC, and there have been studies indicate that combining biomarkers may have more satisfactory effect in the diagnosis and prognosis in NSCLC patients compared with a single genetic or protein biomarker. 17 Hence, researching for more biomarkers which could reinforce the detection rate and prognosis of patients with NSCLC is of urgent need.…”
Section: Discussionmentioning
confidence: 99%
“…The 22 (9.7%) patients treated with osimertinib as second-line agent after dacomitinib showed a median OS of 36.7 months (30.1 to NR), result that was better compared to the median OS reached with chemotherapy as second-line option. However, this result should be interpreted with caution since the number of patients in this group was small [27]. Another retrospective study on the efficacy of second-line osimertinib is the GioTag study [55], a global observational study, assessing as first end-point the time on treatment.…”
Section: Expert Opinionmentioning
confidence: 95%
“…Recently, Mok et al [27] presented the mature results from OS analysis of ARCHER 1050 patient population, after a 30-month follow-up: OS in the dacomitinib group was significantly improved compared to gefitinib (HR 0.760, 95% CI 0.582-0.993, two-sided P = 0.0438), with median OS of 34.1 months with dacomitinib and 26.8 months with gefitinib. It should be noted that this study demonstrated for the first time an improvement in OS, comparing a second-generation EGFR-TKI to a standard of care EGFR-TKI.…”
Section: Phase II and Iii Clinical Studiesmentioning
confidence: 99%